Jejagulan Kendang: Oceanic Fauna as An Inspiration of Musical Concept in Karawitan Bali - Sadguna, I Gde Made Indra; Desiari, Made Ayu (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2023)
The seas and oceans hold profound significance within the cultural and spiritual milieu of the Balinese people. From a theological perspective, the ocean serves as a site for purification and spiritual cleansing, while for artists, it represents an abundant source of creative inspiration. Anecdotes abound regarding the profound influence of marine biodiversity on the composition of musical pieces and conceptualizations within the realm of Balinese karawitan. This scholarly endeavor seeks to undertake a comprehensive analysis of one such musical concept within Balinese culture, known as jejagulan kendang. It is mentioned in the Balinese Language Dictionary that jagul is a large and long fish, often compared to a whale. Although jejagulan kendang is a somewhat ubiquitous term, at times employed with a degree of ambiguity, a rigorous examination of its meaning and implications has hitherto been absent from academic discourse. Consequently, the principal objective of this research is to elucidate the early genesis of jejagulan kendang, tracing its evolution into the contemporary era, and exploring the manner in which marine fauna has served as a wellspring of inspiration for a distinctive musical concept within Balinese karawitan. This research is conducted within the framework of a descriptive-qualitative methodology, with an emphasis on the aesthetic paradigm and the domain of Balinese karawitanology. The empirical data are derived from a multifaceted approach, including in-depth interviews, meticulous observations, and intricate musical analyses of compositions featuring jejagulan kendang. It is envisaged that the findings of this study will provide a comprehensive depiction of the transformation and inspiration derived from oceanic fauna, as they manifest within the musical tapestry of Balinese karawitan. As such, this research is poised to serve as an invaluable reference for Balinese karawitan musicians, both in terms of theoretical knowledge and practical application.